Spatial Coding as a Function of Handedness and Responding Hand: Theoretical and Methodological Implications - Arend, Isabel; Weiss, Peter H.; Timpert, David C.; Fink, Gereon R.; Henik, Avishai (PLOS ONE, 2016)
The Simon effect shows that choice reactions are faster if the location of the stimulus and the response correspond, even when stimulus location is task-irrelevant. The Simon effect raises the question of what factors influence spatial coding. Until now, the effects of handedness, responding hand, and visual field were addressed in separate studies that used bimanual and unimanual tasks, providing inconclusive results. Here we aimed to close this empirical gap by looking at the effects of these variables in the same study. We used a unimanual version of a Simon task with four groups of participants: left-handed and right-handed, responding with the dominant or nondominant hand. Our results show that the Simon effect is substantially reduced in the field of the responding hand for all groups of participants, except for left-handed individuals responding with the left-hand. These findings highlight the importance of attention mechanisms in stimulus-response coding. They reflect that stimulus-response interference is influenced by hierarchical activation of response units. At a practical level, these findings call for a number of methodological considerations (e.g., handedness, responding hand, and visual field) when using stimulus-response conflict to address spatial coding and cognitive control functions in neurological populations.